2016
DOI: 10.1111/jedm.12109
|View full text |Cite
|
Sign up to set email alerts
|

Equating With Miditests Using IRT

Abstract: The equating performance of two internal anchor test structures-miditests and minitests-is studied for four IRT equating methods using simulated data. Originally proposed by Sinharay and Holland, miditests are anchors that have the same mean difficulty as the overall test but less variance in item difficulties. Four popular IRT equating methods were tested, and both the means and SDs of the true ability of the group to be equated were varied. We evaluate equating accuracy marginally and conditional on true abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…(, ) found minitests and semi‐miditests to lead to mostly similar equating (where both non‐IRT equating such as chain linear and equipercentile equating and IRT equating were considered) for data from the critical reading section of the SAT. Fitzpatrick and Skorupski () also found minitests and semi‐miditests, which were internal anchor tests, to lead to mostly similar transformation constants and similar equated ability estimates for simulated data. While most of this research focused on external anchor tests, Fitzpatrick and Skorupski () and Yi () considered internal anchor tests.…”
Section: A Review Of the Performance Of Minitests Versus That Of Midimentioning
confidence: 88%
See 4 more Smart Citations
“…(, ) found minitests and semi‐miditests to lead to mostly similar equating (where both non‐IRT equating such as chain linear and equipercentile equating and IRT equating were considered) for data from the critical reading section of the SAT. Fitzpatrick and Skorupski () also found minitests and semi‐miditests, which were internal anchor tests, to lead to mostly similar transformation constants and similar equated ability estimates for simulated data. While most of this research focused on external anchor tests, Fitzpatrick and Skorupski () and Yi () considered internal anchor tests.…”
Section: A Review Of the Performance Of Minitests Versus That Of Midimentioning
confidence: 88%
“…Fitzpatrick and Skorupski () also found minitests and semi‐miditests, which were internal anchor tests, to lead to mostly similar transformation constants and similar equated ability estimates for simulated data. While most of this research focused on external anchor tests, Fitzpatrick and Skorupski () and Yi () considered internal anchor tests. Together, the above‐mentioned studies demonstrated that equating using miditests and semi‐miditests is as satisfactory as or more satisfactory than equating using minitests for a variety of simulated and real data/tests and equating methods.…”
Section: A Review Of the Performance Of Minitests Versus That Of Midimentioning
confidence: 88%
See 3 more Smart Citations